2012
DOI: 10.1016/j.cell.2012.02.057
|View full text |Cite
|
Sign up to set email alerts
|

A Role for Neuronal piRNAs in the Epigenetic Control of Memory-Related Synaptic Plasticity

Abstract: Summary Small RNA-mediated gene regulation during development causes long-lasting changes in cellular phenotypes. To determine whether small RNAs of the adult brain can regulate memory storage, a process that requires stable and long-lasting changes in the functional state of neurons, we generated small RNA libraries from the Aplysia CNS. In these libraries we discovered an unexpectedly abundant expression of a 28 nucleotide-sized class of piRNAs in brain, which had been thought to be germ-line specific. These… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
469
1
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 504 publications
(493 citation statements)
references
References 48 publications
(58 reference statements)
19
469
1
4
Order By: Relevance
“…In view of our finding of piRNAs in the brain of Aplysia, we have begun to explore their possible presence and roles in the mammalian brain. Consistent with our previous report in Aplysia (10), we demonstrate in the mouse brain, albeit at a low level, the existence of many components of the piRNA pathway by RNA-Seq, immunoprecipitation, and Western blotting ( Fig. 1 and Figs.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In view of our finding of piRNAs in the brain of Aplysia, we have begun to explore their possible presence and roles in the mammalian brain. Consistent with our previous report in Aplysia (10), we demonstrate in the mouse brain, albeit at a low level, the existence of many components of the piRNA pathway by RNA-Seq, immunoprecipitation, and Western blotting ( Fig. 1 and Figs.…”
Section: Discussionsupporting
confidence: 93%
“…Although it has long been thought that piRNA expression and function are restricted to the germline, our laboratory and others have previously found that the piRNA pathway is functional in invertebrate neurons as well (10,11). Aplysia neurons, in particular, have a strikingly abundant expression of piRNAs (contributing to at least 5% of the total noncoding RNA population); they in turn have unique patterns of biogenesis (with most piRNA clusters containing one dominantly expressed piRNA) and predominant nuclear localization (10).…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…The negative correlation between promoter methylation and mRNA expression of galecin in P. fucata was the same with most similar researches in invertebrates. For example, methylation of a CpG island in CREB gene of Aplysia was corresponded to transcriptional repression [33]. The homeobox gene expressions in the Pacific oyster Crassostrea gigas were inversely correlated with their specific DNA methylation [21].…”
Section: Cpg1mentioning
confidence: 99%
“…Initially identified as transcriptional suppressors of transposons in sperm cells, now they have been identified also in non-dividing neurons where they play an important role in the epigenetic control of memory-related synaptic plasticity [Rajasethupathy et al, 2012].…”
Section: American Journal Of Medical Genetics Part Amentioning
confidence: 99%